EVENT MARKETING STRATEGY IN DEVELOPING THE BRAND IMAGE OF MIDEA ELECTRONICS THROUGH THE EVENT “MIDEA BUY WIN FLY 2.0” - Tazkia Nursina; Indah Fajar Rosalina; Wina Puspita Sari; Abdul Kholik; Anggun Nadia Fatimah (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2025)
This study examines how Midea Electronics'